1978
DOI: 10.1136/adc.53.8.664
|View full text |Cite
|
Sign up to set email alerts
|

Familial syndrome with panhypopituitarism, hypoplasia of the hypophysis, and poorly developed sella turcica.

Abstract: SUMMARY Two sisters who died at the ages of 2* 5 years and 5 weeks are described. Both showed signs of panhypopituitarism. At necropsy, no hypophysis could be found in the first child and a rudimentary and partly ectopic hypophysis was found in the other. Both children had a flat, poorly developed sella turcica, and the sellar anomaly could be seen in skull x-rays. These patients represent a hereditary syndrome characterised by neonatal panhypopituitarism, hypoplasia of the pituitary gland, and flat sella turc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…DNA synthesis in thy mus is strongly suppressed in these animals and can be restored by substitutive therapy with GH [14], More recently, it has also been reported that dwarf puppies have a subnormal thymic development associated with a wasting syndrome, and that therapy with bovine GH can prevent such an immunodeficiency [ 15], Few reports concern, at present, the role played by GH in the thymus development and function in humans. Isolated anterior pituitary aplasia is associated with hy poplasia of the thymus in addition to the more obvious hypoplasia of the peripheral endocrine glands [16]. Such observations were made at postmortem examinations.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…DNA synthesis in thy mus is strongly suppressed in these animals and can be restored by substitutive therapy with GH [14], More recently, it has also been reported that dwarf puppies have a subnormal thymic development associated with a wasting syndrome, and that therapy with bovine GH can prevent such an immunodeficiency [ 15], Few reports concern, at present, the role played by GH in the thymus development and function in humans. Isolated anterior pituitary aplasia is associated with hy poplasia of the thymus in addition to the more obvious hypoplasia of the peripheral endocrine glands [16]. Such observations were made at postmortem examinations.…”
Section: Introductionmentioning
confidence: 85%
“…8 were prepu bertal males with a mean chronological age of 12 years (range 9-14) and 3 were pubertal subjects with a mean chronological age of 16 years (range [15][16][17][18], though sexually underdeveloped. 10 healthy age-matched individuals served as control subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a familial syndrome with panhypopi tuitarism, hypoplasia of the pituitary and poorly devel oped sella turcica has been reported [11][12][13] and also an autosomal recessive familial deficiency of growth hor mone and thyrotropin with a large sella turcica [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of sellar vol ume even by CT scanning was considered untrustworthy for reasons mentioned previously. Despite earlier studies corroborating a good correlation between sellar and pitu itary sizes in a normal population [1,29] and in children with congenital pituitary aplasia [33,34], there have been reports to the contrary [4]. The empty sella is the most recognized example of a discrepancy between a small pituitary gland and a large sella [3, 35,36].…”
Section: Discussionmentioning
confidence: 80%